Indonesia Budget and Social Protections; Response to COVID-19 Pandemic - Rizqi Haniyah; Fandy Anggara Putra (Fakultas Ekonomi dan Bisnis Islam UIN Alauddin Makassar, 2021)
This research aims to capture the government's response from the budget side facing an unprecedented health crisis. COVID-19 pandemic disrupts economic activities and negatively impacts the economy on the micro and macro scale. Data from the World Bank stated that Indonesia's poverty level increased from 9.8% to 10.2% during the first six months of the pandemic. The Government of Indonesia immediately responded to the situation by refocusing and expanding the government budget and building the stimulus package named The Covid-19 Pandemic and National Economic Recovery (PEN) to protect citizens' financial well-being and stabilize the macroeconomics condition. The expanded budget leads to the need to find the immediate resources to fulfill the budget deficits. Under the PEN program, the government supports impoverished people with social protection programs. The amount and the type of assistance were adjusted several times due to the spread of COVID-19 cases. Some problems also emerge during the implementation of the protection program, including corruption and recipient mistargeting. The government is expected to improve the program delivery mechanism and develop a system to update recipient data. Digital payment is considered the best way to deliver the benefit to the recipients in order to minimize corruption and accelerate distribution. Regarding the form of assistance, cash transfers are considered the better way to minimize corruption during the delivery process. The coordination between central and local governments should be enhanced to bring the updated data of beneficiaries. Keywords: Budget Allocation; Burden Sharing; COVID-19; National Economic Recovery (PEN); Social Protection;